2006
DOI: 10.1080/14786430500263496
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of long-wavelength phason fluctuations in the i-Al–Pd–Mn quasicrystal

Abstract: We report on the dynamics of phason modes in the i-Al-Pd-Mn icosahedral quasicrystal, measured between room temperature and 650°C, using the Xray Intensity Fluctuation Spectroscopy technique (XIFS). Up to 500°C, the auto-correlation function ℑ(q, t) displays almost no time evolution as expected for frozen-in phason fluctuations at low temperature. At higher temperatures, ℑ(q, t) follows a single exponential time decay from which the characteristic time τ c (q) is extracted. These results are compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 14 publications
(18 reference statements)
2
30
0
Order By: Relevance
“…One then expects diffusive modes with frequency w proportional to iq 2 . This is in agreement with experiments on i-AlMnPd [14].…”
Section: Phasonssupporting
confidence: 82%
“…One then expects diffusive modes with frequency w proportional to iq 2 . This is in agreement with experiments on i-AlMnPd [14].…”
Section: Phasonssupporting
confidence: 82%
“…Then in situ studies were carried out at high temperature and time-dependent phason fluctuations were observed above 873 K (Francoual et al, 2003). In Francoual et al (2006), the dynamics of the phason fluctuations was shown to be of a diffusive type, with a diffusion constant D ? like in equation (23) Charge-density waves (CDW) are observed from Bragg peaks in metals.…”
Section: Fluctuations In Metalsmentioning
confidence: 99%
“…The characteristic time is smaller for longer wavevector and is of the order of 20 to 100 seconds for the wavevector considered. 18,19 The characteristic times go like 1/q 2 as expected for a diffusive mode. The process is energy activated with an activation energy equal to about 3 eV.…”
Section: Marc De Boissieumentioning
confidence: 91%